Rapid anterior capsular contraction after phacoemulsification surgery in a patient with retinitis pigmentosa - Jin-Poi T (Dove Medical Press, 2013)
Tan Jin-Poi, Ismail Shatriah, Sonny Teo Khairy-Shamel, Embong ZunainaDepartment of Ophthalmology, School of Medical Sciences, Universiti Sains Malaysia, Kubang Kerian, MalaysiaAbstract: A decrease in the anterior capsule opening after cataract surgery has been observed in eyes with weakened lens zonules. It commonly occurs in diabetes mellitus, uveitis, pseudoexfoliation syndrome, high myopia, and elderly patients. Herein, we report the case of a middle-aged man with advanced retinitis pigmentosa who developed a rapid contraction of the anterior capsule after an uneventful phacoemulsification surgery that resulted in severe visual loss during the early postoperative period.Keywords: contraction of anterior capsule, early postoperative period, phacoemulsification surgery, retinitis pigmentosa